Drugs and (dis)order household survey in Nimroz Province, Afghanistan, 2021 - Koehler, Jan (UK Data Service, 2022)
Dataset resulting from a questionnaire-based household survey with 975 households in Nimroz province, Afghanistan. The survey focused on economic activities, the drug economy, security and safety, governance structures within communities, relations with the state, the provision of services and health consequences from drug consumption. The survey was carried out in 50 villages in four districts of Nimroz province, and is complemented with village history profiles of the 50 same villages (UKDA-SN-854923). It forms part of wider research to develop a robust and dynamic understanding of the actors, commodities and events that shape the borderlands of Afghanistan, in particular with regards to opium production, trade and use, and associated insecurity and conflicts. Drugs & (dis)order is a Global Challenges Research Fund (GCRF) project generating new evidence on how to transform illicit drug economies into peace economies in Afghanistan, Colombia and Myanmar. By 2030, more than 50% of the world’s poor will live in fragile and conflict-affected states. And many of today’s armed conflicts are fuelled by illicit drug economies in borderland regions. Trillions of dollars have been spent on the War on Drugs, but securitised approaches have failed. In fact, they often increase state fragility and adversely affect the health and livelihoods of communities and households. In light of these failures, there’s increasing recognition that drug policies need to be more pro-poor and aligned with the Sustainable Development Goals (SDGs). But the evidence base for this policy reform is patchy, politicised and contested. Drugs & (dis)order is helping to generate pro-poor policy solutions to transform illicit economies into peace economies. To do this we will: (1) Generate a robust evidence base on illicit drug economies and their effects on armed conflict, public health and livelihoods. (2) Identify new approaches and policy solutions to build more inclusive development and sustainable livelihoods in drugs affected contexts. (3) Build a global network of researchers and institutions in Afghanistan, Colombia, Myanmar and the UK to continue this work.